Pelatihan Penulisan Artikel dan Manajemen Jurnal SMP Negeri 10 Kota Depok, Jawa Barat - Syamruddin Syamruddin; Irwansyah Irwansyah; Oki Iqbal Khair; Ahmad Fitriansyah; Rita Rita; Tannia Regina (Indonesian Journal of Society Engagement, 2021)
As professionals, apart from educating and teaching, teachers are also required to express their ideas, thoughts, ideas, and intellectual intelligence in published written form. The obligation to write is part of the teacher's performance in the context of continuous professional development as a system of career development and teacher work performance. Therefore it is necessary to make training for teachers on article writing and journal management through Community Service (PkM) activities. The purpose of this PkM is to provide tips and tricks to teachers about article writing and journal management. The results obtained during the service activities are that the teachers have been able to make journal articles based on the results of their research. Then understand the process of publishing articles in relevant journals, especially for teachers at SMP Negeri 10 Depok City, West Java. Thus the teacher's writing is increasingly known. Through this service activity, teachers understand how journal management is. Training on article writing and journal management for teachers of SMP Negeri 10 Depok City, West Java was very useful. With PkM which is packaged in the form of training activities, it is easier for teachers to make quality journal articles. In addition, teachers are also able to manage and publish their own journals in their schools. Abstrak Sebagai tenaga professional, selain mendidik dan mengajar, guru-guru juga dituntut untuk mengungkapkan ide, pikiran, gagasan, dan kecerdasan intelektualnya dalam bentuk tulisan yang terpublikasikan. Kewajiban menulis merupakan bagian dari kinerja guru dalam rangka pengembangan keprofesian berkelanjutan sebagai sistem pembinaan karir dan prestasi kerja guru. Oleh karena itu perlu dibuat pelatihan bagi guru-guru tentang penulisan artikel dan manajemen jurnal melalui kegiatan Pengabdian kepada Masyarakat (PkM). Tujuan PkM ini untuk memberikan tips dan trik kepada guru tentang penulisan artikel dan manajemen jurnal. Hasil yang diperoleh selama kegiatan pengabdian yaitu guru-guru telah mampu membuat artikel jurnal berdasarkan hasil penelitiannya. Kemudian memahami proses penerbitan artikel pada jurnal yang relevan, terutama bagi guru-guru di SMP Negeri 10 Kota Depok, Jawa Barat. Dengan demikian tulisan guru semakin dikenal. Melalui kegiatan pengabdian ini, guru-guru memahami bagaimana manajemen jurnal. Pelatihan penulisan artikel dan manajemen jurnal bagi guru-guru SMP Negeri 10 Kota Depok, Jawa Barat sangat bermanfaat. Dengan adanya PkM yang dikemas dalam bentuk kegiatan pelatihan, guru-guru semakin mudah membuat artikel jurnal yang berkualitas. Selain itu guru-guru juga mampu mengelola dan menerbitkan jurnal sendiri di sekolah mereka. Kata Kunci: guru; penulisan; artikel; manajemen; jurnal